Noddy meets Santa. - Blyton, Enid. (New York : HarperEntertainment, 1999)
Noddy is excited because Santa Claus is coming to Toyland.
"Based on the television series Noddy, a BBC Worldwide Ltd/Enid Blyton Ltd/Catalyst Entertainment Inc, co-production"--Colophon.
"First published in the United Kingdom in 1994 by BBC Children's Books"--Colophon.
"Noddy."
"Original animated series produced by Cosgrove Hall Films, based on the books by Enid Blyton"--Colophon.
3.0
K-3
Keywords: Christmas -- Fiction; Santa Claus -- Fiction; Toys -- Fiction; Christmas -- Fiction; Santa Claus -- Fiction; Toys -- Fiction